'"Demo" and "cracy"': music, trust, and authentication in Mexico's 2018 elections. Issue 3 (4th May 2023) - Green, Andrew
ABSTRACT: Taking as its focal point the Mexican national elections of 2018, this article explores how music, often circulated in the form of online videos, has responded to low political trust in an emerging multiparty system. It explores home-made videos made to foment trust in the election's eventual victor, and a project funded by the National Electoral Institute (INE) to use rap to facilitate informed participation in the elections. It engages with the literature on musical 'authenticity' to discuss what it explores as two forms of musical 'authentication': one personal, which authenticates or vouch for individual political leaders, and another systemic, looking to foment legitimacy by supporting voters' ability to verify political claims. This article thus contributes to the understanding of political systems undergoing democratic transitions, arguing for attention to democratization as an affective, creative, and multiple process.